Overweight and Associated Factors: A Study in Adults from the Interior of Northeast Brazil - Santos, Paula Thianara de Freitas; Oliveira, Juliana Souza; Leal, Vanessa Sá; Lira, Pedro Israel Cabral de; Oliveira, Marcela Claudia de Paula; Correia Junior, Marco Aurelio de Valois; Costa, Emília Chagas (Acta Scientiarum. Health Sciences, 2025)
To verify the occurrence of overweight and associated factors in adults of a region in the inland of northeast Brazil. A cross-sectional study of population based with probability sampling, involving adults aged 20 to 59 years. Data collection was based on anthropometric measurements of weight and height, according to the World Health Organization, in addition to the application of a questionnaire comprising questions referring to demographic, socioeconomic, behavioral and presence of chronic diseases. Overweight was determined for body mass index (IMC) ≥ 25kg/m². The logistic regression analysis was used to assess the association between overweight and the variables explanations. A number of 345 individuals were evaluated. The prevalence of overweight was 54.4%. In the final model, it was witnessed 105 overweight females (OR = 2.36; IC95%: 1.177-4.758; p = 0.016), age 30 to 39 years old (OR = 2.12; IC95%: 1.016 – 4.435; p = 0.045), and those who hypertension (OR = 3.18; IC95%: 1.337-7.587; p = 0.009). More than half of the population of adults from an inland region of north-eastern Brazil were overweight, corroborating the context of nutritional transition present in several parts of our country and of the world. In addition, the factors sex, age and hypertension were associated with this profile, conferring a multifactorial characteristic in the etiology of this problem.